2023
DOI: 10.1063/5.0143552
|View full text |Cite
|
Sign up to set email alerts
|

An efficient decoherence scheme for fewest switches surface hopping method

Abstract: The fewest switches surface hopping method, in its original form, is known to be over-coherent. An accurate and efficient decoherence scheme is still a question of concern in the community. We propose a modification of the augmented fewest switches surface hopping (A-FSSH) scheme to make it efficient without compromising on its accuracy. We compare our proposed decoherence scheme with a recently proposed parameter-free decoherence scheme by Wang and co-workers. We show that for all model systems investigated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To incorporate nonadiabatic transitions, stochastic hopping is allowed between different PESs. Numerous studies have demonstrated that FSSH outperforms the conventional Ehrenfest mean field dynamics in many situations. In the past years, the deficiencies of FSSH have been well identified. For instance, the electronic wave function in FSSH is propagated as a pure state and thus is generally overcoherent. Fortunately, if we are interested only in populations of adiabatic states, a great deal of studies has shown that the occupation of active states is superior to the electronic wave function, ,, which partially bypasses the overcoherence issue. Proper analysis of electronic coherence from the trajectory ensemble, however, is also nontrivial.…”
Section: Introductionmentioning
confidence: 99%
“…To incorporate nonadiabatic transitions, stochastic hopping is allowed between different PESs. Numerous studies have demonstrated that FSSH outperforms the conventional Ehrenfest mean field dynamics in many situations. In the past years, the deficiencies of FSSH have been well identified. For instance, the electronic wave function in FSSH is propagated as a pure state and thus is generally overcoherent. Fortunately, if we are interested only in populations of adiabatic states, a great deal of studies has shown that the occupation of active states is superior to the electronic wave function, ,, which partially bypasses the overcoherence issue. Proper analysis of electronic coherence from the trajectory ensemble, however, is also nontrivial.…”
Section: Introductionmentioning
confidence: 99%